Structural Design and Motion Analysis of Carbon-free Trolleys Based on the RSSR Mechanism - He Long; Zhang Ya; Wang Furong; Han Zifeng; Ji Zhaohui (Jixie chuandong)
Aimed at the problems of track deviation and lack of reference for debugging during the movement of carbon-free trolleys, the RSSR mechanism is selected as the steering device, and the mathematical model of obstacle avoidance motion of the trolley is established based on the motion characteristics of the spatial four-bar linkage. The influence of the parameters of the spatial four-bar linkage on the trajectory of the trolley is analyzed from the kinematics point of view, the influence of the parameters of the four-bar linkage on its motion process is further explored from the dynamics point of view, and the general law of the trolley motion of the RSSR mechanism is obtained. Finally, the actual debugging of the trolley shows that the trolley can run smoothly and successfully avoiding 30 obstacles. The mathematical model established and movement law of the car obtained from the research of the RSSR mechanism are of great engineering guiding significance for the actual debugging of carbon-free trolleys.